Levels of physical activity and sitting time in women with infants, toddlers and preschoolers: a population-based cross-sectional study. (January 2023) - Makama, M.; Brown, W.J.; Lim, S.; Skouteris, H.; Harrison, C.L.; Joham, A.E.; Mishra, G.D.; Teede, H.; Moran, L.J.
Abstract: Objectives: Insufficient physical activity (PA) and prolonged sitting time (ST) increase the risk of chronic disease and mortality. Caring for young children can potentially impact maternal PA and sedentary behaviours. The aims of this study were to explore the levels of PA and ST in women with young children (infants, toddlers and preschoolers) and sociodemographic and behavioural factors associated with these. Study design: This was a population-based cross-sectional study. Methods: Survey 5 data collected in 2009 ( n = 4290) of the 1973–1978 birth cohort of the Australian Longitudinal Study on Women's Health were used. Multiple linear and logistic regression models were used to examine associations. Results: In adjusted models, compared with women with preschoolers, women whose youngest child was an infant aged 0–6 months, aged >6–12 months or toddler had lower PA (−321.3 MET.min/week [95% confidence interval (CI) −416.2, −226.4], −147.9 MET.min/week [95% CI −237.6, −58.1] and −106.4 MET.min/week [95% CI −172.3, −40.5]). ST was higher in women whose youngest child was an infant aged 0–6 months (0.48 h/day; 95% CI 0.19, 0.77) but lower with infants aged >6–12 months (−0.33 h/day; 95% CI −0.60, −0.05) and toddlers (−0.40 h/day; 95% CI −0.60, −0.20) than in those with preschoolers. The findings were similar in the logistic model. Sociodemographic and behavioural factors such as occupation and marital status also influenced PA and ST. Conclusions: Women with infants and toddlers have lower PA than women with preschoolers. Women are more likely to sit more in the first 6 months after childbirth. These findings can inform resources and intervention development to improve activity levels in women with young children through consideration of the age of the youngest child, sociodemographic and behavioural factors.